Konsep Jual Beli Online dalam Perspektif Filsafat Islam dan hukum indonesia: Analisis Nilai-Nilai Kejujuran, Keadilan, dan Kemaslahatan dalam Transaksi Jual Beli - Andry Nirwanto; Dian Anggraeni; Kurniati (4, 2025)
This study analyzes the concept of online buying and selling from the perspective of Islamic philosophy and Indonesian law, focusing on the values ​​of honesty, justice, and benefit as the primary principles in digital transactions. With the advancement of technology, online buying and selling practices have become an integral part of modern economic activity, yet simultaneously require strengthening moral and regulatory aspects. Islamic philosophy provides an ethical foundation through the principles of *shidq* (honesty), *‘adl* (justice), and *maslahah* (benefit), which emphasize the importance of information transparency, prohibition of fraud, and balance of rights and obligations between sellers and buyers. Meanwhile, Indonesian law, through the Electronic Information and Transactions (ITE) Law, the Consumer Protection Law, and other related regulations, provides a legal framework that ensures legal certainty, consumer protection, and order in electronic transactions. The results of this discussion indicate that Islamic philosophy and Indonesian law have strong convergence in upholding morality and integrity in online buying and selling practices. The integration of these two perspectives can create a digital trading ecosystem that is not only efficient and modern, but also civilized and oriented towards social benefit. This synergy strengthens digital transaction governance to align with spiritual values ​​and applicable legal norms. This research confirms that implementing the values ​​of honesty, justice, and welfare is not merely a normative requirement, but also a practical necessity for building trustworthy, sustainable, and responsible online buying and selling practices. Therefore, the integration of Islamic ethics and national legal regulations is a crucial foundation for realizing a digital economic system that is fair, dignified, and in line with the noble values ​​of Indonesian society. Abstrak Penelitian ini menganalisis konsep jual beli online dalam perspektif filsafat Islam dan hukum Indonesia dengan fokus pada nilai kejujuran, keadilan, dan kemaslahatan sebagai prinsip utama dalam transaksi digital. Seiring berkembangnya teknologi, praktik jual beli online menjadi bagian integral dari aktivitas ekonomi modern, namun di sisi lain menuntut penguatan aspek moral dan regulatif. Filsafat Islam memberikan landasan etis melalui prinsip shidq (kejujuran), ‘adl (keadilan), dan maslahah (kemanfaatan) yang menekankan pentingnya transparansi informasi, larangan penipuan, serta keseimbangan hak dan kewajiban antara penjual dan pembeli. Sementara itu, hukum Indonesia melalui UU ITE, Undang-Undang Perlindungan Konsumen, dan regulasi terkait lainnya menyediakan kerangka hukum yang memastikan terwujudnya kepastian hukum, perlindungan konsumen, dan ketertiban dalam transaksi elektronik. Hasil pembahasan menunjukkan bahwa filsafat Islam dan hukum Indonesia memiliki titik temu yang kuat dalam menegakkan moralitas dan integritas dalam praktik jual beli online. Integrasi kedua perspektif ini mampu menciptakan ekosistem perdagangan digital yang tidak hanya efisien dan modern, tetapi juga berkeadaban dan berorientasi pada kemaslahatan sosial. Sinergi tersebut memperkuat tata kelola transaksi digital agar selaras dengan nilai spiritual dan norma hukum yang berlaku. Penelitian ini menegaskan bahwa penerapan nilai kejujuran, keadilan, dan kemaslahatan bukan sekadar tuntutan normatif, tetapi juga kebutuhan praktis untuk membangun praktik jual beli online yang amanah, berkelanjutan, dan penuh tanggung jawab. Dengan demikian, integrasi etika Islam dan regulasi hukum nasional menjadi fondasi penting dalam mewujudkan sistem ekonomi digital yang adil, bermartabat, dan sesuai dengan nilai luhur masyarakat Indonesia